Interaction Between AtCML9 and AtMLO10 Regulates Pollen Tube Development and Seed Setting - Zhang, Qian; Hou, Congcong; Tian, Yudan; Tang, Mitianguo; Feng, Changxin; Ren, Zhijie; Song, Jiali; Wang, Xiaohan; Li, Tiange; Li, Mengou; Tian, Wang; Qiu, Jinlong; et al. (Frontiers in Plant Science, 2020)
In higher-plant reproduction, the compatibility of pollen tube germination in pistil is essential for successful double fertilization. It has been reported that Mildew Locus O (MLO) family gene NTA (MLO7), expressing in synergid cells, can correctly guide pollen tubes. However, the molecular mechanism underlying the interacting partners to MLOs in the fertilization is still unknown. In our study, we identified the direct protein interaction between CML9 and MLO10 within a non-canonical CaMBD. In GUS reporter assays, CML9 expresses in a high level in pollens, whereas MLO10 can be specifically detected in stigma which reaches up to a peaking level before fertilization. Therefore, the spatio-temporal expression patterns of MLO10 and CML9 are required for the time-window of pollination. When we observed the pollen germination in vitro, two cml9 mutants dramatically reduced germination rate by 15% compared to wild-type. Consistently, the elongation rate of pollen tubes in planta was obviously slow while manually pollinating cml9-1 pollens to mlo10-1 stigmas. Additionally, cml9-1 mlo10-1 double mutant had relatively lower rate of seed setting. Taken together, protein interaction between MLO10 and CML9 is supposed to affect pollen tube elongation and further affect seed development.